Alfred Dreyfus Man, Milieu, Mentality and Midrash - Simms, Norman (Academic Studies Press, 2008)
This groundbreaking book focuses on Alfred Dreyfus the man, with emphasis placed on his own writings, including his recently published prison workbooks and his letters to his wife Lucie. Through close reading of these documents, a much more sensitive, intellectual, and Jewish man is revealed than was previously suspected. He and Lucie, through their family connections and mutual loyalty, were interested in and supported the artistic, scientific, philosophical and historical movements that formed their Parisian milieu. But as an Alsatian Jew, Alfred was also critical of many aspects of technological and ideological developments, making his mentality one of skepticism as well as idealism.